1980
DOI: 10.1002/jcu.1870080104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound criteria for in utero diagnosis of microcephaly

Abstract: Microcephaly (small head) is clinically important only if there is concomitant micrencephaly (small brain). Extensive studies on patients in mental institutions have shown that there is close correlation among microcephaly, micrencephaly, and mental retardation when the head is more than three standard deviations below the norm. If the small head is less than two standard deviations below the norm, no strong correlation exists with eigher small brain or mental retardation. High-resolution ultrasound permits im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…A few studies have tried to investigate the correlation between neurodevelopmental delay and isolated microcephaly but with conflicting results. One study showed the risk of neurodevelopmental delay to be 10.5% when head circumference is between two and three standard deviations below the mean,4 while others showed no significant difference 3435…”
Section: What Is the Prognosis And Postnatal Follow-up?mentioning
confidence: 99%
“…A few studies have tried to investigate the correlation between neurodevelopmental delay and isolated microcephaly but with conflicting results. One study showed the risk of neurodevelopmental delay to be 10.5% when head circumference is between two and three standard deviations below the mean,4 while others showed no significant difference 3435…”
Section: What Is the Prognosis And Postnatal Follow-up?mentioning
confidence: 99%
“…Para que essa segurança seja transmitida, é necessário que tal exame seja feito em vários períodos da gravidez, de modo a permitir diferentes diagnósticos de acordo com a época do aparecimento de seus primeiros sinais. Por exemplo, os defeitos de fusão do tubo neural poderão ser detectados a partir da décima primeira semana de gestação, se for utilizado um transdutor vaginal; o funcionamento da bexiga entre dezoito e vinte semanas; o perfil dos lábios, que possibilitam o diagnóstico de fendas labiais, a partir da vigésima semana; a defasagem do crescimento do fêmur nos diferentes nanismos, através de exames seqüenciais, a partir de doze semanas; a hidrocefalia, a partir de quatorze semanas, e a microcefalia, por diferentes avaliações, dependendo da época e da etiologia para ela se manifestar (-Kurtz et al, 1980). Não se pode admitir nos dias de hoje que somente após o nascimento se diagnostiquem malformações que poderiam ser detectadas durante a gestação pelo ultra-som, como, por exemplo, a ausência de dedos, de mãos ou até de membros.…”
Section: Diagnóstico Ultra-sonográficounclassified
“…It is defined as a head circumference (HC) >3 standard deviations below the mean or below the second percentile for gestational age (GA) (2)(3)(4). These definitions, however, continue to be a matter of considerable controversy (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%